Talent Management as a Conceptual Framework for Driving Bureaucratic Reform in Public Organizations - Rita Suartini; Veithzal Rivai Zainal; ⁠Azis Hakim (Dinasti Review, 2025)
Public sector organizations around the world are under increasing pressure to reform outdated bureaucratic systems in order to improve service delivery, transparency, and organizational performance. However, these reforms often face significant obstacles related to rigid human resource practices, low employee engagement, and insufficient leadership capabilities. This paper proposes the use of talent management as a conceptual framework to drive bureaucratic reform in public organizations. Talent management encompasses a strategic set of practices, including talent identification, development, deployment, and retention, aimed at maximizing the potential of human capital. By integrating these practices into the reform process, public institutions can cultivate a more agile, innovative, and performance-driven workforce. The conceptual framework presented in this study is derived from a comprehensive literature review and is intended to guide policymakers, HR practitioners, and organizational leaders in designing effective talent strategies that align with the goals of bureaucratic transformation.